1991
DOI: 10.1002/j.2048-7940.1991.tb01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Nursing Approaches to Cerebrovascular Accident: A Comparison of Two Approaches

Abstract: The purpose of this study was to compare patients receiving neurodevelopmental therapy (NDT) to patients receiving a traditional approach. The study took place on two separate medical rehabilitation units, each using just one approach. Patients were assigned to each unit based upon bed availability. The charts of 43 cerebral vascular accident (CVA) patients who received the traditional approach and of 37 CVA patients who received NDT were audited for demographic, functional, and disposition data. No significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
12
1
Order By: Relevance
“…A quasi‐experimental approach is used to compare the functional gains of stroke patients treated with the Bobath technique and those treated with the traditional nursing approach to determine any differences between the two groups. Unlike previous research by Lewis (1986), Salter et al . (1991 ) could find no significant differences between the groups.…”
Section: Evaluation Of Specific Nursing Interventionscontrasting
confidence: 67%
See 1 more Smart Citation
“…A quasi‐experimental approach is used to compare the functional gains of stroke patients treated with the Bobath technique and those treated with the traditional nursing approach to determine any differences between the two groups. Unlike previous research by Lewis (1986), Salter et al . (1991 ) could find no significant differences between the groups.…”
Section: Evaluation Of Specific Nursing Interventionscontrasting
confidence: 67%
“…(1991 ) could find no significant differences between the groups. However, Salter et al . (1991 ) report the possibility of a type 11 error, meaning that the sample may have been too small to show differences between the two groups.…”
Section: Evaluation Of Specific Nursing Interventionsmentioning
confidence: 99%
“…Selected trials refer to effectiveness of general treatment (10)(11)(12)(13)(14)(15), treatment aimed at lower limb and/or gait (16)(17)(18)(19)(20)(21) and upper limb (22)(23)(24). Population characteristics are summarized in Tables III, V and VII, and study characteristics in Tables IV, VI and VIII.…”
Section: Resultsmentioning
confidence: 99%
“…Most earlier studies have not demonstrated any benefits of BB therapy on the various outcomes, such as HRQoL (13), functional status (11,12,14,18,20,34,35), depression (12) or arm function (19). Only 2 studies have showed improved functional status as a result of BB therapy; one small retrospective study (16) and one comparing BB therapy with an orthopaedic treatment (17).…”
Section: Discussionmentioning
confidence: 99%